Avaliação comportamental de camundongos expostos ao teste de aversão condicionada ao contexto induzida pela interação social agressiva - Penagos Gil, Jeimmy Marion (2018)
Rodents exposed to social defeat stress exhibit hormonal, behavioral, and autonomic responses called defense reactions. This study sought to conduct a behavioral validation of a context aversion generated by social defeat test. Ninety-eight male albino Swiss mice were habituated for 10 minutes for three consecutive days to an apparatus, containing a tunnel-bound burrow, which leads to a surface (divided by a wire mesh) that has two parts of the same dimensions : Surfaces A (site of social interactions with physical contact) and surface B (location of social interactions without physical contact). The burrow, the tunnel and the surface A are separated from each other by guillotine doors. From the 4th to the 7th day, the animals were distributed in: (a) control group (animals exposed to social interaction with non-aggressive conspecific), (b) defeated group (animals exposed to social interaction with a dominant conspecific), exposed to 5 minutes of sensory interaction. In this interaction an aggressor or non-aggressor mouse was placed on surface B separated from the other animal by the wire mesh, followed by social defeat or non-aggressive interaction on surface A for 3 minutes. Subsequently, aggressive or non-aggressive animals were placed on surface B for a further 5 minutes, to the adapted test of interaction with the conspecific (same context where they were habituated). Following the same protocol, but in a new context (social interaction box), group (c) control - new context was exposed to social interaction with a non - aggressive cospecific, and group (d) defeated - new context was exposed to interaction with a dominant co-specific. On the eighth day, all animals were individually exposed to the Adapted test of interaction with the conspecific for 10 minutes, without the presence of the coespecific, but containing a portion of the sawdust of their housing cage. On the third day of Habituation and on the Day of Reexposure, the following measures were recorded: frequency of entrances and time spent in the burrow, tunnel and surface A; frequency and time of rising and grooming; SAP total time and time to dig on the surface. When compared to the Hab stage, on the eighth day the GD had a decrease of rising, the permanence time on surface A and excavation of the sawdust, as well as increase in the frequency and time of grooming in the burrow and in the frequency of total SAP stretched. Analysis of the results did not reveal any signs of environmental avoidance in GC, GDn or GCn animals. Our results showed that the use of four social defeats preceded by or followed by sensory exposure to the aggressor opponent causes aversion conditioned to the context of the clash.